Pluralismo y virtudes en los clásicos. Una relectura de la práctica sabiduría aristotélica - Perine, Marcelo (Estudios de Filosofía, 2008)
The present reflection starts from the book VI of Ethics to Nicomachus and the results of a previous study on Aristotle's phrónesis, in which each Aristotelian phrónesis is not a contemplative science, but a practical wisdom is immediately directed to action. for the knowledge of the particulars and the means to reach the fines proposed by the action. This practical wisdom is true and, therefore, normative and that universally connects the end of human life. In fact, for Aristotle the phrónesis is a habitual cognitive state, they are rational, which presupposes a non-rational volitional state and a non-strictly rational cognitive state, which is experience.